The Relationship Of Participation In Pregnancy Exercise With The Duration Of The Second Stage Of Labor In Primigravida - Novita Br Ginting Munthe; Mega Wati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
The duration of labor has a risk of causing perinatal death twice as high as normal delivery. The duration of this second stage in primiparas and multiparas is different, namely in primiparas it lasts 1.5-2 hours while in multiparas it lasts 0.5-1 hours. Efforts that can be made by pregnant women so that delivery runs smoothly can be controlled by doing pregnancy exercises. This study aims to determine the relationship between participation in pregnancy exercise and the duration of the second stage of labor in primigravida at the Pratama Bunda Tessa Lubuk Pakam Clinic in 2022. This type of research is a quantitative study with a descriptive correlation design through a cross sectional approach. The population of this study were all primigravida mothers who had delivered at the Mother Tessa Primary Clinic as many as 30 people. The sampling technique used a total sampling of 30 people. The research instrument used a questionnaire sheet which was analyzed using the chi-square test. The results showed that 50% of primigravida mothers who followed pregnancy exercise routinely and 50% who did not participate in pregnancy exercise. The duration of the second stage of labor in primigravida was normal (46.7%), fast (33.3%) and slow (20%). Through the chi-square test obtained p-value = 0.006. The conclusion of this study is the relationship between pregnancy exercise participation and the duration of the second stage of labor in primigravida. So it is hoped that the Mother Tessa Primary Clinic will provide Health Education to pregnant women about the causes of the length of labor, especially in the second stage. And it is also hoped that the clinic can maintain and implement policies for implementing pregnancy exercise for pregnant women, especially primigravida mothers, in an effort to maintain fitness and prepare physically and mentally in the delivery process.